Palestinian Flags in Jakarta: Urban Protests and Symbolic Resistance in the Indonesian Capital (Palestine Issues on Indonesian Society, 2025)
This paper examines the role of urban protests and symbolic resistance in Jakarta, focusing on the prominent use of the Palestinian flag as a symbol of solidarity and political activism. Through an analysis of public demonstrations, protests, and street art in Jakarta, the study investigates how the Palestinian flag has become a powerful visual tool in Indonesian protests, representing both local resistance to perceived injustice and global solidarity with Palestine. The paper explores how the flag is used as a symbol not only of support for Palestine but also as a marker of broader political sentiments, including anti-imperialism, resistance to foreign intervention, and solidarity with marginalized communities. By analyzing protests in key urban spaces such as Jakarta’s central squares and streets, the study reveals how symbolic resistance has taken shape in the Indonesian capital, examining its role in shaping public discourse and influencing political activism. The paper also reflects on the impact of these protests on Indonesian political culture, highlighting how such urban movements challenge political elites and contribute to the discourse on justice, human rights, and international solidarity.